De Novo donor-specific anti-HLA antibody risk stratification in kidney transplantation using a combination of B cell and T cell molecular mismatch assessment - Chou-Wu, Elaine; Niemann, Matthias; Youngs, Danny; Gimferrer, Idoia (Frontiers in Immunology, 2025)
IntroductionThe presence of de novo donor-specific antibody (dnDSA) has detrimental effect on allograft outcomes in kidney transplantation. As humoral responses in transplantation are elicited targeting non-self-epitopes on donor HLA proteins, assessing HLA mismatches at the molecular level provides a refined means for immunological risk stratification.MethodsIn the present study, we utilized three HLA molecular mismatch assessment algorithms, Snow, HLAMatchmaker, and PIRCHE-II, to evaluate the independent and synergistic association of B cell and T cell epitope mismatches with dnDSA development in a cohort of 843 kidney transplant recipients.ResultsOur results demonstrated that B cell and T cell epitope mismatches at HLA Class I and DRB1/DQB1 loci are remarkably increased in dnDSA-positive recipients, even after normalization by allele mismatch numbers in individual study subjects. Furthermore, elevated Snow, verified eplet mismatches, and PIRCHE-II scores are significantly associated with dnDSA occurrence individually and in combination.ConclusionOur findings highlight the value of utilizing B cell and T cell epitope mismatch evaluation in living donor selection and immunological risk stratification to improve transplant outcomes.